A review on the graphical user authentication algorithm : recognition-based and recall-based. - Ugochukwu, Ejike Ekeke Kingsley; Jusoh, Yusmadi Yah (Advanced Institute of Convergence Information Technology, 2013)
User authentication has become an important consideration in information security as traditional password-based schemes are constantly subjected to attacks. Graphical images have now taken center stage as they are easier to remember and offer other security features. In this paper, we explore two categories of the Graphical User Authentication Algorithm: Recognition-based and Recall-based. Examples from both categories are presented to compare the types of attacks encountered, usability and security.